The Potential for Less Invasive Inference of Resource Use: Covariation in Stable Isotope Composition between Females and Their Eggs in Bluegill. Issue 2 (25th February 2015) - Colborne, Scott F.; Hain, Timothy J. A.; Longstaffe, Fred J.; Neff, Bryan D.
Abstract: Stable isotope analysis is frequently used to examine resource use in wild populations, but it often involves invasive or lethal methods of collecting tissue samples. The development of less invasive or nonlethal sampling techniques will expand the possible uses of stable isotopes. We examined whether fish eggs meet three basic requirements for inferring female resource use from them: (1) the isotope composition of the eggs is correlated with that of other maternal tissues for which isotope composition is known to be related to diet; (2) the isotope composition remains constant over the egg development period; and (3) dietary inferences using eggs are similar to those for other maternal tissues. Using artificial crosses, we tested the relationship between eggs and two commonly sampled maternal tissues (white muscle and liver) in wild‐caught Bluegills Lepomis macrochirus . We found that egg isotope composition was strongly correlated with that of other maternal tissues, particularly liver, and remained constant from prefertilization to the day of hatch, with no change in 13 C and an increase of only 0.3‰ in 15 N. Furthermore, the results of SIAR (Stable Isotope Analysis in R) mixing models indicated a large degree of overlap in diet estimates between eggs and the other maternal tissues. Overall, eggs can be reliably used to infer the prebreeding foraging ecology of female Bluegills throughout the egg development period. Received July 10, 2014; accepted October 28, 2014